A review of animal health and drug use practices in India, and their possible link to antimicrobial resistance - Mutua, Florence K.; Sharma, G.; Grace, Delia; Bandyopadhyay, S.; Shome, B.; Lindahl, Johanna F. (Springer, 2020)
Background Livestock production, particularly the dairy sector, is important for food and nutritional wellbeing of communities in India, it supports livelihoods of many farmers, and contributes to the economy of the country. India is a high consumer of antibiotics and antimicrobial resistant (AMR) bacteria are a major public health concern. Objectives Our objectives were to identify animal health and drug use practices that may contribute to emergence and spread of AMR in the country, review previous AMR- mitigation strategies, and discuss “theory of change” as an approach to informing the choice of interventions. Methods We undertook a desk review of literature to identify practices with potential to contribute to emergence and spread of antimicrobial resistance in India. Searches were done in PubMed, Google scholar, and Google. Data were synthesized and discussed by themes. Results Animal disease surveillance is less developed and infrastructure to support delivery of services is inadequate. Several groups are known to offer animal health services. The untrained “animal health workers” and para-veterinarians are more popular with farmers as they charge less for consultations (compared to veterinarians who are few and charge more). Over-the-counter access of antibiotics, without prescription, and direct marketing of drugs to farmers are common. Because of this, farmers are able to treat their animals and only consult when cases become non- responsive to treatment. Antibiotics are mostly used in management of mastitis cases. Drug withdrawal periods are rarely observed and occurrence of antibiotic- contaminated milk has been reported. Awareness on AMR is low and antimicrobial stewardship in livestock is yet to be developed. Initiatives such as the National programme for containment of AMR, National Action Plan on AMR, and the National Health policy point to government’s commitment in addressing the problem of AMR in the country. Conclusion Several animal health and drug use practices, with potential to cause AMR, have been described, and their contribution can be discussed further by engaging stakeholders in a “theory of change” exercise. Interventions that address AMR from the animal health perspective should be promoted, and incentives to increase their adoption explored.